Global trends in research on miRNA–microbiome interaction from 2011 to 2021: A bibliometric analysis - Yan, Xiang-Yun; Yao, Jun-Peng; Li, Yan-Qiu; Zhang, Wei; Xi, Meng-Han; Chen, Min; Li, Ying (Frontiers in Pharmacology, 2022)
An increasing number of studies have shown that the microRNA (miRNA)–microbiome interaction plays a crucial role in host health and diseases. This bibliometric analysis aimed to identify the status of global scientific output, research hotspots, and frontiers regarding the study of miRNA–microbiome interaction over the past decade. We retrieved miRNA–microbiome-related studies published from 2011 to 2021 from the Web of Science Core Collection database; the R package bibliometrix was used to analyze bibliometric indicators, and VOSviewer was used to visualize the field status, hotspots, and research trends of miRNA–microbiome interplay. In total, 590 original articles and reviews were collected. A visual analysis of the results showed that the number of publications has increased substantially with time. China produced the most papers, and the United States contributed the highest number of citations. Shanghai Jiaotong University and the University of California Davis were the most active institutions in the field. Most publications were published in the areas of biochemistry and molecular biology. Yu Aiming was the most prolific writer, as indicated by the h-index and m-index, and Liu Shirong was the most commonly co-cited author. A paper published in the International Journal of Molecular Sciences in 2017 had the highest number of citations. The keywords “expression” and “gut microbiota” appeared most frequently, and the top three diseases that appeared among keywords were colon cancer, inflammatory bowel disease, and neurological disorders. This bibliometric study revealed that most studies have focused on miRNAs (e.g., miR-21, miR-155, and miR-146a), gut microbes (e.g., Escherichia coli, Bifidobacterium, and Fusobacterium nucleatum), and gut bacteria metabolites (e.g., butyric acid), which have the potential to improve the diagnosis, treatment, and prognosis of diseases. We found that therapeutic strategies targeting the miRNA–microbiome axis focus on miRNA drugs produced in vitro; however, some studies suggest that in vivo fermentation can greatly increase the stability and reduce the degradation of miRNA. Therefore, this method is worthy of further research.